Evaluating a simple blending approach to prepare magnetic and stimuli-responsive composite hydrogel particles for application in biomedical field - H. Ahmad; M. S. Sultana; M. A. Alam; M. M. Rahman; K. Tauer; M. A. Gafur; M. K. Sharafat (eXPRESS Polymer Letters, 2016)
The inclusion of super paramagnetic iron oxide (Fe3O4) nanoparticles in stimuli-responsive hydrogel is expected to enhance the application potential for cellular therapy in cell labeling, separation and purification, protein immobilization, contrasting enhancement in magnetic resonance imaging (MRI), localized therapeutic hyperthermia, biosensors etc. in biomedical field. In this investigation two different magnetic and stimuli-responsive composite hydrogel particles with variable surface property were prepared by simply blending Fe3O4/SiO2 nanocomposite particles with stimuli-responsive hydrogel particles. Of the hydrogel particles prepared by free-radical precipitation polymerization poly(styrene-N-isopropylacrylamide-methyl methacrylate-polyethylene glycol methacrylate) or P(S-NIPAM-MMA-PEGMA) was temperature-sensitive and poly(S-NIPAM-methacrylic acid-PEGMA) or P(S-NIPAM-MAA-PEGMA) was both temperature- and pH-responsive. The morphological structure, size distributions and volume phase transitions of magnetic and stimuli-responsive composite hydrogel particles were analyzed. Temperature-responsive absorptions of biomolecules were observed on both magnetic and stimuli-responsive Fe3O4/SiO2/P(S-NIPAM-MMA-PEGMA) and Fe3O4/SiO2/P(S-NIPAM-MAA-PEGMA) composite hydrogel particles and separation of particles from the dispersion media could be achieved by applying magnetic field without time consuming centrifugation or decantation method.